Optimization design and experiment of the variable differential gear train planting mechanism - Zhao, Xiong; Liu, Ziwei; Jia, Yuanwu; Ma, Xingxiao; Zhang, Pengfei; Chen, Jianneng (International Journal of Agricultural and Biological Engineering, 2024)
In order to improve the adaptability of the planting mechanism for different plant spacings, a variable differentialgear train planting mechanism based on precise pose and trajectory control was proposed by combining the open chain 2R rodgroup and the variable differential gear train. According to the pose requirements of receiving seedling point, transportingseedling point and planting point, three precise pose points of constrained planting trajectory were determined. Through thethree-position motion generation structural synthesis method, combined with computer-aided optimization design software, aset of mechanism parameters that meet the planting requirements were optimized. Based on the optimized mechanismparameters, by only changing the coordinates of two trajectory shape control points, three planting trajectories with key pointposition information adapted to 300 mm, 400 mm and 500 mm plant spacing were obtained by interpolation, and three pairs oftotal transmission ratio of three groups of variable differential gear trains were calculated. When distributing the totaltransmission ratio of the mechanism, the fixed axis gear train and the differential gear train are combined. The fixed axis geartrain included a pair of non-circular gear pairs and a pair of positive gear pairs, which were convenient for disassembly andassembly. The former drives the sun gear at variable speed, and the latter drives the planet carrier at uniform speed. Based onthis structure, the transmission ratio of the positive gear pair is –1, and the transmission ratio of the differential gear train is 0.5.The sub-transmission ratio of the single-stage non-circular gear pair was calculated and the pitch curves of three pairs of non-circular gears were solved. Three pairs of non-circular gear pairs with different transmission ratios were replaced in turn andthree sets of planting mechanisms were modeled in three dimensions. The virtual prototype motion simulation was completedby ADAMS software, and the physical prototype was built for vegetable pot seedling planting test. The theoretical solution wasconsistent with the attitude and trajectory of the actual test. When the test sample size was 100 plants, the actual average plantspacing was measured to be 303 mm, 402 mm, and 503 mm, with errors of 1.3%, 1.25%, and 1.88%. The width of the movinghole was 72 mm, 70 mm, and 71 mm, and the planting success rate were 94%, 96%, and 95%. The test results verified thecorrectness of the optimization design results of the mechanism, indicating that the variable differential gear train plantingmechanism can adapt to a variety of plant spacing and has good planting effect. Keywords: plant spacing, planting mechanism, variable differential gear train, precise pose, trajectory control, parameteroptimization DOI: 10.25165/j.ijabe.20241702.8238 Citation: Zhao X, Liu Z W, Jia Y W, Ma X X, Zhang P F, Chen J N. Optimization design and experiment of the variable differential gear train planting mechanism. Int J Agric & Biol Eng, 2024; 17(2): 85–93.